Perdamaian Dalam Kasus Pidana (Kecelakaan Lalu Lintas) Melalui Hukum Adat Di Desa Timpah - Paramita Dewi, Ni Putu; Kastama, I Made; Darman, I Komang; Peni, Gelar Sumbogo (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
The Dayak tribe is one of the communities in Indonesia that still applies customary law as a guideline in regulating the lives of its people in various matters, including in terms of resolving problems, including traffic accidents. Conflict resolution through Customary Law will better represent the feelings and desires of the community because the law itself comes from the community itself. Customary Law seeks to resolve conflicts or problems with peace for the parties. Peace is a goal that all parties aspire to. Traditional institutions play a very important role in regulating the behavior patterns of indigenous communities, especially the Dayak indigenous community. Traffic accident cases are also one of the rights and permits for Let Adat to implement, this is stated in Article 10 of Central Kalimantan Regional Regulation No. 16 of 2008. Based on this, it clearly states that the existence of the Damang Traditional Head's permission to resolve the abilities that arise in cases of traffic accidents is included in the case of giving Singer. A traffic accident that takes someone's life is called a Sahiring Customary Violation (taking someone's life). The aim of implementing problem resolution through customary law is to achieve peace between the parties and restore the disturbed balance. Singer Sahiring is a singer or fine for murder or someone who takes the life of another person